MODELS AND METHODS OF BORROWED CAPITAL’S MANAGEMENT OF THE ENTERPRISE - AZAROVA, Anzhelika; KRAIEVSKA, Аlla; MIRONOVA, Yuliia; LITUN, Maxim (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Raised capital is a part of the enterprise's capital, which is formed at the expense of external sources, such as loans, credits, issuance of securities, etc. Raised capital, such as loans, bonds, shares or investments, is an important part of financing a business. It is an important tool for financing the company's activities, but at the same time it is associated with certain risks.Achieving effective management of this capital helps to ensure sustainable operation and growth of the enterprise, ensure financial stability and the ability to pay interest or repay loans on time. A business must determine the optimal mix of financing that meets its needs and constraints.Effective management of capital employed can help a company to be more competitive in the market, as it helps to influence the cost of capital and overall financial profitability.Factors affecting the capital structure include the organizational and legal form of the enterprise, industry specifics of operational activity, the size of the enterprise, the cost of capital, the freedom to choose sources of financing, the state of the capital market and the level of income taxation. Regular determination of capital management efficiency indicators is important for monitoring the current state of its structure.The important issues related to the effective use of loans and other forms of borrowed capital to achieve the company's financial goals are considered in the article. Debt management strategies and tools, optimization of debt service costs, as well as risks associated with the use of borrowed capital were studied.
Keywords: management of raised capital; debt capital; financial stability; equity capital; market conditions; cost of capital